Sierra Leone : Economic Development Documents-National Development Plan, 2019-23. (IMF Staff Country Reports; Country Report ;, 2019)
The Government of Sierra Leone's new Medium-term National Development Plan (MTNDP) 2019-2023 has been founded on a strong political commitment to deliver devel-opment results that would improve the welfare of Sierra Leone's citizens. The plan charts a clear path towards 2023 en route to the goal of achieving middle-income status by 2039 through inclusive growth that is sustainable and leaves no one behind. For the next five years, the Free Quality School Education Programme is the government's flagship programme to provide a solid base to enhance human capital development and to facilitate the transformation of the economy.